キョクイキ カクシュ ミズシリョウ チュウ ノ テイノウド HTO ソクテイ ノ タメノ デンカイ ノウシュク ヲ フクメタ エキタイ シンチレーション ホウ ノ ケントウ - 神山, 孝吉; カミヤマ, コウキチ; 五十嵐, 誠; イガラシ, マコト; Kamiyama, Kokichi; Igarashi, Makoto (2000)
P(論文) 水素原子の同位体の一つであるトリチウムは水分子を構成し, 水の起源, 循環過程を研究するトレーサーとして有効である。過去には核実験で多量に生成されたが, 自然界では宇宙線と大気との相互作用によって成層圏などで生成されている。その後地球上の水循環過程に取り込まれ時間とともに放射崩壊していく。そのため海洋のように長い滞留時間を有する海水中のトリチウム濃度は比較的低く, 大気中の水蒸気を起源とする降水中のトリチウム濃度は高い。本研究では, 各種極域水試料について濃縮操作を含めてトリチウム測定方法を提案した。海水起源の水蒸気で構成されている降水試料, 滞留時間の長い雪氷試料や海氷試料などの低濃度のトリチウム測定, また成層圏起源の水蒸気を含んだ高濃度のトリチウム測定について, 処理方法や測定時間など実験計画を立案するための基礎資料を提出した。 Tritium (T) is one of the hydrogen isotopes, composing water molecules designated HTO, and is useful as a tracer of water origin and circulation. T has been produced as fission debris, and is also produced naturally in the stratosphere by the interaction of cosmic radiation with air atoms. HTO is introduced into the water circulation process in the earth, where T is diminished by nuclear decay. Higher HTO content in the water occurs in the direct deposition from the atmosphere. Lower HTO content occurs in the water reservoirs where the residence time of water is longer such as ocean. The deposition, consist of the water vapor from the oceanic origin, has also lower HTO content. The content in sea ice depends on the origin of water, oceanic or atmospheric. This paper discusses the method for the HTO measurement of natural water with lower HTO content, including the procedure of the condensation and distillation. The water samples in the polar region have various HTO content and the analytical time, ranged from several days to several months, depends mainly on HTO content. The proposal on the procedure of the measurement, depending on the samples in various water reservoirs in the polar region, is available for conducting the analytical plan for water samples in the natural environments with the various residence times, especially for the samples under low HTO content. departmental bulletin paper